Communication and Information Technologies Annual [New] Media Cultures. - Laura Robinson; Jeremy Schulz; Shelia R. Cotten; Timothy Hale; Apryl Williams (Studies in Media and Communications ,, 2016)
Sponsored by the Communication and Information Technologies Section of the American Sociological Association, this volume examines wide-ranging aspects of culture, communication, and [new] media broadly defined. Themes include the interplay between [new] media and any of the following: culture, communication, technology, convergence, the arts, cultural production, and cultural change in the digital age. Contributions shed light on emergent phenomena that sociologists, particularly those studying media or communication, culture scholars will find intriguing.